The origins and dynamic changes of C3- and S100A10-positive reactive astrocytes after spinal cord injury - Zhao, Qing; Ren, Yi-long; Zhu, Yan-jing; Huang, Rui-qi; Zhu, Rong-rong; Cheng, Li-ming; Xie, Ning (Frontiers in Cellular Neuroscience, 2023)
Accumulating studies focus on the effects of C3-positive A1-like phenotypes and S100A10-positive A2-like phenotypes of reactive astrocytes on spinal cord injury (SCI), however the origins and dynamic changes of C3- and S100A10-positive reactive astrocytes S100A10-positive reactive astrocytes after SCI remain poorly understood. Through transgenic mice and lineage tracing, we aimed to determine the origins of C3- and S100A10-positive reactive astrocytes S100A10-positive reactive astrocytes. Meanwhile, the distribution and dynamic changes in C3- and S100A10-positive reactive astrocytes S100A10-positive reactive astrocytes were also detected in juvenile and adult SCI mice models and cultured astrocytes. Combing with bulk RNA sequencing (RNA-seq), single-cell RNA sequencing (scRNA-seq) and bioinformatic analysis, we further explored the dynamic transcripts changes of C3- and S100A10-positive reactive astrocytes after SCI. We confirmed that resident astrocytes produced both C3- and S100A10-positive reactive astrocytes, whereas ependymal cells regenerated only S100A10-positive reactive astrocytes in lesion area. Importantly, C3-positive reactive astrocytes were predominantly activated in adult SCI mice, while S100A10-positive reactive astrocytes were hyperactivated in juvenile mice. Furthermore, we observed that C3- and S100A10-positive reactive astrocytes had a dynamic transformation process at different time in vitro and vivo, and a majority of intermediate states of C3- and S100A10-positive reactive astrocytes were found during transformation. RNA-seq and scRNA-seq results further confirmed that the transcripts of C3-positive reactive astrocytes and their lipid toxicity were gradually increased with time and age. In contrast, S100A10-positive reactive astrocytes transcripts increased at early time and then gradually decreased after SCI. Our results provide insight into the origins and dynamic changes of C3- and S100A10-positive reactive astrocytes after SCI, which would be valuable resources to further target C3- and S100A10-positive reactive astrocytes after SCI.